Anisotropic stellar models admitting conformal motion - Banerjee, Ayan; Banerjee, Sumita; Hansraj, Sudan; Övgün, Ali (Springer Heidelberg, 2017)
We address the problem of finding static and spherically symmetric anisotropic compact stars in general relativity that admit conformal motions. The study is framed in the language of f(R) gravity theory in order to expose opportunity for further study in the more general theory. Exact solutions of compact stars are found under the assumption that spherically symmetric spacetimes admit conformal motion with anisotropic matter distribution in nature. In this work, two cases have been studied for the existence of such solutions: first, we consider the model given by f(R) = R and then f(R) = aR + b. Finally, specific characteristics and physical properties have been explored analytically along with graphical representations for conformally symmetric compact stars in f(R) gravity.
Keywords: F R; Modified Gravity; Cosmological Constant; Compact Stars; Inflation; Universe; Tests